What is obesity - epidemiology - Blakemore, Alexandra (Henry Stewart Talks, 2016)
Obesity: a global epidemic (epidemiology), Obesity in the past, Evolutionary perspective, Obesity harms everyone, Obesity does not affect all populations equally